2010
DOI: 10.1186/1475-2875-9-119
|View full text |Cite
|
Sign up to set email alerts
|

Candidate malaria susceptibility/protective SNPs in hospital and population-based studies: the effect of sub-structuring

Abstract: BackgroundPopulations of East Africa including Sudan, exhibit some of the highest indices of genetic diversity in the continent and worldwide. The current study aims to address the possible impact of population structure and population stratification on the outcome of case-control association-analysis of malaria candidate-genes in different Sudanese populations, where the pronounced genetic heterogeneity becomes a source of concern for the potential effect on the studies outcome.MethodsA total of 72 SNPs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 20 publications
4
27
1
2
Order By: Relevance
“…Other factors such as population structure and chance, as well as the experimental design or the phenotype(s) of malaria diagnosed in a given study, may impact the conclusions. Efforts to use genomics approaches and genome-wide association analysis have been initiated (Ayodo et al, 2007;Timmann et al, 2007;The Malaria Genomic Epidemiology Network, 2008;Jallow et al, 2009;Eid et al, 2010) and some new regions of potential malaria resistance have been identified.…”
Section: Resistance Mutantsmentioning
confidence: 99%
“…Other factors such as population structure and chance, as well as the experimental design or the phenotype(s) of malaria diagnosed in a given study, may impact the conclusions. Efforts to use genomics approaches and genome-wide association analysis have been initiated (Ayodo et al, 2007;Timmann et al, 2007;The Malaria Genomic Epidemiology Network, 2008;Jallow et al, 2009;Eid et al, 2010) and some new regions of potential malaria resistance have been identified.…”
Section: Resistance Mutantsmentioning
confidence: 99%
“…24 Our analysis of infecting parasite genotypes and treatment outcome did not show any strong and independent association between known parasite resistance markers and treatment response. The host immune response represents a key factor that may interfere in the relationship between levels of drug resistant markers and observed treatment failure 35,36 in in vivo drug studies. In individuals exposed to malaria for their first time, infection with the malaria parasite does not always lead to severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the sample size was determined to test for clinical efficacy and safety and not for association analysis, which would have been much larger. In addition, the contribution of minor alleles in defining treatment outcomes would be possible only with very large samples size and population substructuring as was observed in a hospital-based and population-based study 35 evaluating candidate malaria susceptibility/resistant genes. Nevertheless, these findings flag the involvement of IL-22, IL-4R1, IL-10, IL-17, CD36, and TNF-SM2 in protective responses to malaria infections and treatment in Cameroonian children.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The past decade has seen growing evidence of ethnic differences in susceptibility to malaria and of the diverse genetic adaptations to malaria that have arisen in different populations. The fact that different malaria-resistance alleles have arisen in different places suggests that a great deal of selection by malaria has happened relatively recently in human history and certainly since human migration out of Africa (Eid et al, 2010). Such population differences in susceptibility to malaria are becoming more amenable to study since the development of high through-put genetic technology, thereby allowing us to genetically dissect the outcome of infection.…”
Section: Genetic Association Studies and The Post-genomic Eramentioning
confidence: 99%